2018
DOI: 10.3390/w11010017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Factors for Controlling Sediment Connectivity of Landslide Materials: A Flume Experiment

Abstract: Connectivity of landslide sediment to and within fluvial systems is a key factor affecting the extent of mobilization of hillslope material. In particular, the formation of landslide dams and the transformation into landslide-induced debris flows represent “end members” of landslide sediment mobility. To quantify sediment connectivity, we developed a two-segment flume representing tributary inflow and the main channel. Mobility of sediment was examined by combinations of various topographic factors, such as tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Good results were obtained to predict the stability of the bank. [10] studied the effect of the bed slope and the angle of flow on the transportation of sediment using an acrylic flume by applying different proportions of moisture content The results showed that the collapse volume increases with the increasing the angle of flow and the bed slope when the moisture content was greater than the degree of saturation or less.…”
Section: Introductionmentioning
confidence: 99%
“…Good results were obtained to predict the stability of the bank. [10] studied the effect of the bed slope and the angle of flow on the transportation of sediment using an acrylic flume by applying different proportions of moisture content The results showed that the collapse volume increases with the increasing the angle of flow and the bed slope when the moisture content was greater than the degree of saturation or less.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic nature of subsurface hydrology depends on the complex interactions among precipitation inputs, physical properties and heterogeneity of soils and bedrock, local geomorphology, and vegetation and associated biomass. These factors influence the timing of landslides with respect to precipitation inputs and antecedent soil moisture [14][15][16][17], the mass and mode of failure [18], and the extent of runout or transformation of landslides into debris flows [19].Both the infiltration of rainwater and snowmelt and bedrock exfiltration provide the local trigger of these landslides, while drainage and evapotranspiration tend to stabilize hillslopes by rerouting and removing subsurface water. Subsurface hydrology is strongly affected by preferential flow within the soil, substrate topography, and exfiltration from fractures in bedrock [2,13,18,[20][21][22]; the overall regolith moisture regime and recharge rates are influenced by evapotranspiration, soil development processes, soil water-groundwater interactions, and landform aspect and shape [14,16,[23][24][25].…”
mentioning
confidence: 99%
“…This dynamic nature of subsurface hydrology depends on the complex interactions among precipitation inputs, physical properties and heterogeneity of soils and bedrock, local geomorphology, and vegetation and associated biomass. These factors influence the timing of landslides with respect to precipitation inputs and antecedent soil moisture [14][15][16][17], the mass and mode of failure [18], and the extent of runout or transformation of landslides into debris flows [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation